Vitamin B12 deficiency presenting as pseudo-thrombotic microangiopathy: a case report and literature review - Fahmawi Y (Dove Medical Press, 2019)
Yazan Fahmawi,1 Yesica Campos,1 Moh’d Khushman,2 Omar Alkharabsheh,2 Ashish Manne,2 Haseeb Zubair,2 Saadia Haleema,3 Jacek Polski,3 Sabrina Bessette11Department of Internal Medicine, University of South Alabama, Mobile, AL, USA; 2Department of Hematology-Oncology, Mitchell Cancer Institute, University of South Alabama, Mobile, AL, USA; 3Department of Pathology, University of South Alabama, Mobile, AL, USACorrespondence: Yazan FahmawiDepartment of Internal Medicine, University of South Alabama, 2451 USA Medical Center Drive, Mobile, AL 36617, USATel +1 251 471 7891Fax +1 251 470 1652Email yfahmawi@health.southalabama.eduAbstract: Pseudo-thrombotic microangiopathy (pseudo-TMA) is a recognized, yet uncommon, clinical presentation of vitamin B12 deficiency. Patients with pseudo-TMA present with microangiopathic hemolytic anemia (MAHA), thrombocytopenia and schistocytes. They are often misdiagnosed as thrombotic thrombocytopenia purpura (TTP) and receive unnecessary therapy. Here, we report a case of a 60-year-old male who presented with thrombocytopenia and normocytic normochromic anemia. Anemia work-up was remarkable for severe B12 deficiency (<60 pg/mL) and a positive non-immune hemolysis panel. Peripheral smear was reviewed and showed anisocytes, poikilocytes, schistocytes and hypersegmented neutrophils. Vitamin B12 replacement (1000 mcg IM daily) was started, ADAMTS13 activity was sent and daily plasmapheresis was initiated. Over the next 3 days, the patient’s hemoglobin and platelets were stable and the hemolysis panel showed gradual improvement. On day 4, ADAMTS13 activity results came back normal at 61%. Accordingly, plasmapheresis was discontinued, parenteral B12 replacement was continued and that resulted in gradual improvement and eventually cessation of hemolysis and normalization of hemoglobin and platelets. In this patient, parietal cell autoantibodies were positive and so the diagnosis of pernicious anemia was made. Patients with severe vitamin B12 deficiency may present with features mimicking TTP such as MAHA, thrombocytopenia and schistocytosis. An early and accurate diagnosis of pseudo-TMA has a critical clinical impact with respect to administering the correct treatment with vitamin B12 replacement and avoiding, or shortening the duration of, unnecessary therapy with plasmapheresis.Keywords: vitamin B12 deficiency, pseudo-thrombotic microangiopathy, schistocytes